Od obrazu do sentencji. O grafice Sławomira Mrożka - Seweryna Wysłouch (Przestrzenie Teorii)
The author analyses co-existence of visual and language signs in Mrozek's drawings. Because of the kind of mutual relations, seven types of signs are distinguished. These are: 1. visual autonomous signs; 2. comic strips (stories in drawings); 3. iconic multimeaning sign; 4. iconic sign - interpreting of the language sign; 5. language sign - interpreting of iconic sign; 6. language sign reduced to the plan of expression; 7. iconic sign as a pretext to introduce language communication. The analysis shows the relational character of language signs in heterogenic communications and vast possibilities of iconic signs which, apart from conveying simple information, are capable of interpreting concepts and ridicule mechanisms of language manipulation. It also allows to speak about the evolution of Mrożek's work.